Molecular survey of tick-borne infectious agents in cricetid rodents (Rodentia: Cricetidae) in Central and Southern Chile - Ardila, Marlon Mauricio; Thomas, Richard; Santodomingo, Adriana; Silva-de la Fuente, María C.; Muñoz-Leal, Sebastián; Landaeta-Aqueveque, Carlos; Henríquez, AnaLía (Frontiers in Veterinary Science, 2024)
Tick-borne infectious agents (TBIAs) include several bacteria and protozoa that can infect vertebrates, including humans. Some of these agents can cause important diseases from both a public health perspective, such as Lyme disease, and from an animal health and production viewpoint, such as Texas fever. In Chile, several studies have assessed the presence of tick-borne disease agents in vectors and mammal hosts, mainly in the northern regions, but few studies have assessed the presence of these agents in Central and Southern Chile. This study aimed to assess the presence of three groups of TBIAs—Borrelia, Anaplasmataceae, and Piroplasmida—in cricetid rodents of Central and Southern Chile. A total of 207 specimens from 13 localities between the O’Higgins and Los Lagos regions were captured. DNA was extracted from the liver and spleen, and subsequently underwent polymerase chain reaction (PCR) amplification targeting the 16S rRNA, flaB, and 18S rRNA genes to detect DNA from Borrelia, Anaplasmataceae, and Piroplasmida, respectively. Although no DNA from these TBIAs was detected, the DNA extraction process was validated by optimal DNA purity ratios (an A260/A280 ratio within the 1.6–2.0 range) and successful internal control amplification in all samples. These results, in addition to findings from previous reports, suggest a very low prevalence of these TBIAs in the rodent population studied. Further research into the factors influencing the presence of these agents and their vectors will provide insight into the reasons underlying this low prevalence.